Caretaker Government and the Evolution of Caretaker Conventions in New Zealand - Boston, Jonathan; Levine, Stephen; McLeay, Elizabeth; Roberts, Nigel S; Schmidt, Hannah (Victoria University of Wellington Law Review, 1998)
Since the financial crisis immediately following the 1984 general election, various efforts have been made to clarify the role and responsibilities of caretaker governments in New Zealand. The need to do so was given added urgency as a result of the referendum in 1993 in favour of proportional representation. This article examines the recent evolution of New Zealand's caretaker conventions and assesses their application following the first MMP election in late 1996. The article begins with a brief description of caretaker conventions in other parliamentary democracies. It then considers the operation of the caretaker conventions in New Zealand under the previous first-past-the-post electoral system, and discusses the measures taken in the early-to-mid 1990s to clarify these conventions in preparation for MMP. Having evaluated the conduct of government during the lengthy interregnum in late 1996, the article concludes with an analysis of some of the continuing policy issues generated by caretaker governments and outlines possible ways of reducing the frequency and duration of caretaker periods.